Development of a new generation vaccine for the canine distemper virus (CDV). An in silico, in vitro and in vivo approach (2024)
ABSTRACT: this thesis is structured into four chapters, each one addressing a research question focused on the development of a next-generation vaccine against canine distemper virus (CDV). Each chapter covers topics that address diverse aspects to answer this question, providing the reader with not only theoretical context but also in silico, in vitro, and in vivo experimental results for the development of a new immunization strategy for domestic and wild species affected by CDV. The first chapter delves into the theoretical framework of virus biology, discussing themes such as the replication cycle, pathogenesis, clinical presentation, and virus-host interaction. This chapter provides the reader with the biological and molecular context of CDV. The second chapter presents a systematic literature review with a scoping approach to determine the current status of CDV vaccination in domestic and wild species. This chapter is developed in this thesis because there has been no comprehensive study summarizing the current state of vaccine development for controlling CDV spread and infection. A total of 2,321 articles identified and 68 studies were eligible based on predefined inclusion criteria focusing on CDV vaccines across various animal species including canines, ferrets, minks, mice, and others. Research efforts originated from scientific communities from the United States, Canada, France, and Denmark. Diverse vaccine formulations, a wide range of immunization routes and schedules were observed. Safety and efficacy underscored the significance of these immunogens within the evaluated animal populations. Among these findings is the inclusion of 37 studies which conducted post-immunization CDV challenge assessments, predominantly in canine subjects, pointing the survival outcomes among vaccinated populations. Nonetheless, substantial gaps in vaccine research were identified, particularly in wildlife reservoirs. Thus, collaborative endeavors are imperative for the formulation of effective vaccination strategies aimed at preserving animal welfare and attenuating the worldwide repercussions of CDV, particularly among endangered species. The third chapter presents the development of immunogenic peptides derived from the genetic and antigenic information of all CDV variants circulating worldwide using computational tools for the development of a universal CDV vaccine, followed by safety assessment in silico and in vitro. An immunogenic CDV peptide-based candidate was developed, utilizing a peptide library derived from consensus sequences of CDV H and F proteins from circulating strains worldwide. Computational tools were employed to assess the immunogenic potential of these peptides. Molecular docking and dynamic simulations were utilized to evaluate the molecular interaction of selected peptides with canine MHC-I, -II, TLR-2, and -4. In silico safety was assessed through antigenicity, allergenicity, toxicity potential, and comparison with homologous canine peptides, while in vitro safety was evaluated through cytotoxicity assays using cell lines, canine peripheral blood mononuclear cells (cPBMCs), and hemolysis potential assays with canine red blood cells. Subsequently, a multiepitope CDV polypeptide was synthesized based on the most promising peptides, and the in silico and in vitro evaluations were conducted to compare it with single immunogens. At this stage, five peptide candidates were identified, both individually and as a multiepitope CDV polypeptide, for evaluation as a next-generation peptide-based vaccine in an animal model. The final chapter involves the evaluation of immunogenic peptides either individually or as a polypeptide in an in vivo mouse model to determine their safety and immunogenicity in a vaccine formulation with a commercial adjuvant. Twenty-four BALB/c mice were distributed into four groups and subjected to three different vaccine dosing regimens over a 28-day period. Seroconversion was determined using ELISA, while cellular immune responses were measured via flow cytometry, specifically focusing on activation-induced markers (AIMs). Both the peptide mixture, multiepitope CDV polypeptide and commercial vaccine (CV) were safe in mice, with statistically significant seroconversion observed in the groups vaccinated with the multiepitope CDV polypeptide and the CV compared to the control group. Furthermore, mice immunized with the multiepitope CDV polypeptide exhibited increased levels of antigen-specific CD4+ CD134+ and IFN-γ+ T cells, CD8+ T cells, as well as TNF-α and IL-6-producing cells compared to the placebo group. These experimental results collectively indicated seroconversion for the multiepitope CDV polypeptide lower than the CV vaccine and the establishment of cellular immune memory. The development of multiepitope polypeptide vaccines presents a promising preventive strategy against CDV, and our integrated approach represents a significant advancement in the development of new immunization candidates or alternative to enhance current vaccination efficacy for controlling CDV disease and its spread among domestic dogs and wildlife animals. Therefore, this doctoral thesis addresses the need to update vaccination strategies against CDV through an in silico, in vitro, and in vivo approach for the development of a vaccine platform based on immunogenic peptides derived from the genetic information of relevant viral agents, with a universal character necessary for controlling the infection, spread, and transmission of highly prolific viruses such as CDV.